The association between corporate governance and firm performance – a meta-analysis - Siddiqui, Sayla Sowat (© 2015 Emerald Group Publishing Limited, 2016)
This article was published in International Journal of Accounting and Information Management [© 2015 Emerald Group Publishing Limited] and the definite version is available at: http://dx.doi.org/10.1108/IJAIM-04-2014-0023 The article website is at: http://www.emeraldinsight.com/journal/ijaim